La participación sectorial en los Servicios Sociales del Ayuntamiento de Fuenlabrada - García Andrés, Rosa María (Miscelánea Comillas, 2010)
The participation in Fuenlabrada's Social Services is organized by the Local Advisory Board of Social Services which was created in 1991, as the most important community participation body. Also it has been organized in three forums of participation: emigrants, teenager and people with disabilities. Furthermore, there are other participation’s mechanism such as the recently created Local Observatory of Dependence and other areas where the citizens can be directly involved: Volunteer Program, Intercultural Local Agents and the Pro-moter Group of Participation and Development.